3D Structural View of Pathogen Recognition by Mammalian Lectin Receptors - Manabe, Noriyoshi; Yamaguchi, Yoshiki (Frontiers in Molecular Biosciences, 2021)
Humans and other mammals resist exogenous pathogens by recognizing them as non-self. How do they do this? The answer lies in the recognition by mammalian lectin receptors of glycans usually found on the surface of pathogens and whose chemical structure is species-specific. Some glycan components, such as galactofuranose, only occur in microbes, and is the principal means by which mammalian lectin receptors recognize non-self. Several lectins may function together as pattern recognition receptors to survey the infecting pathogen before the adaptive immune system is invoked. Most lectins have primary and secondary monosaccharide-binding sites which together determine the specificity of a receptor towards microbial glycans. There may also be a hydrophobic groove alongside the sugar binding sites that increases specificity. Another elaboration is through oligomerization of lectin domains with defined spacing and arrangement that creates high-affinity binding towards multiply-presented glycans on microbes. Microbe-specific polysaccharides may arise through unique sugar linkages. Specificity can come from mammalian receptors possessing a shallow binding site and binding only internal disaccharide units, as in the recognition of mannan by Dectin-2. The accumulation of 3D structural information on lectins receptors has allowed the recognition modes of microbe glycans to be classified into several groupings. This review is an introduction to our current knowledge on the mechanisms of pathogen recognition by representative mammalian lectin receptors.